The Social Structuration of Six Major Social Media Platforms in the United Kingdom: Facebook, LinkedIn, Twitter, Instagram, Google+ and Pinterest - Blank, G; Lutz, C (Association for Computing Machinery, 2016)
Sociological studies on the Internet have often examined digital inequalities. These studies show how Internet access, skills, uses and outcomes vary between different population segments. However, we know more about social inequalities in general Internet use than in social media use. Especially, we lack differentiated statistical evidence of the social profiles of distinct social media platforms. To address this issue, we use a large survey data set in the United Kingdom and investigate the social structuration of six major social media platforms. We find that age and socio-economic status are driving forces of several -- but not all -- of these platforms. Aggregating platform adoption into a general measure of social media use blurs some of the subtleties of more fine-grained indicators, namely platform uses and specific activities, such as status updating and commenting.